Transformational Leadership Interaction In Developing Personnel Quality At Ma'had An-Nahla Lhokseumawe City - Candra Rahmat Sanjaya; Almuhajir; Rahmy Zulmaulida (STAI Terpadu Yogyakarta, 2023)
This study aims to explain the interaction of transformational leadership in developing the quality of personnel at Ma'had An-Nahla Lhokseumawe City. This research is a type of qualitative field research with a descriptive approach. The data needed in this study are narrative and descriptive data sourced from research subjects namely Ma'had Leaders, Principals, Teachers, and Administrative Personnel with data collection techniques of interviews, observation, and documentation as well as analysis techniques consisting of data presentation, data reduction, and conclusion drawing. The results showed that the interaction of transformational leadership in developing the quality of personnel of principals, teachers and administrative staff at Ma'had An-Nahla consisted of: gaining respect from subordinates, believing in others, building challenges within the organisation, providing motivation, group spirit, showing the leader's efforts to encourage subordinates to be more innovative and creative, and all individuals get special attention.